IMPLEMENTASI METODE BACKPROPAGATION DALAM KLASTERISASI OBJEK - Santika, Diaz D; Susanti, Betsy; Anderson, Willy; Wongso, Kanisius (Bina Nusantara University, 2007)
Aim of the research was to prove that backpropagation method could be implemented for image recognitionwhile doing object classification. Observational method done was to do library research by reading and searching forinformation from various sources, then conduct analysis upon data, and last, design the application from analysisresults. From the evaluation that has been done, the result for accuration and speed are high enough (above 95%). Afteranalyzing evaluation result, it is concluded that backpropagation method could be implemented for object classification.